Self‐Organization Postprocess for Additive Manufacturing in Producing Advanced Functional Structure and Material. Issue 6 (4th December 2021) - Chi, Jinchun; Agea Blanco, Boris; Bruno, Giovanni; Günster, Jens; Zocca, Andrea
Abstract : Additive manufacturing (AM) is developing rapidly due to its flexibility in producing complex geometries and tailored material compositions. However, AM processes are characterized by intrinsic limitations concerning their resolution and surface finish, which are related to the layer‐by‐layer stacking process. Herein, a self‐organization process is promoted as an approach to improve surface quality and achieve optimization of 3D minimal surface lightweight structures. The self‐organization is activated after the powder bed 3D printing process via local melting, thereby allowing surface tension‐driven viscous flow. The surface roughness R a (arithmetic average of the roughness profile) could be decreased by a factor of 1000 and transparent lenses and complex gyroid structures could be produced for demonstration. The concept of self‐organization is further elaborated by incorporating external magnetic fields to intentionally manipulate magnetic particles, which are mixed with the polymer before printing and self‐organization. This concept can be applied to develop programmable materials with specific microtextures responding to the external physical conditions. Abstract : Herein, a self‐organization postprocess that can remarkably improve the surface quality and density from the powder bed 3D‐printed porous matrix is presented, while achieving topological optimization of minimal surface lightweight structures. Self‐organization is realized by local melting which enables a viscous flow driven by surface tension. Consequently a gyroid structure with an optical transparent area in the center is achieved.